Voting on Redistribution with Tax Evasion - Rainald Borck (Deutsches Institut für Wirtschaftsforschung (DIW), 2003)
This paper analyzes voting on a linear income tax which is redistributed lump sum to the taxpayers. Individuals can evade taxes, which leads to penalties if evasion is detected. Since preferences satisfy neither single peakedness nor single crossing, an equilibrium may not exist. When it does exist, it may have interesting properties, in particular, the poor and the rich may form a coalition against the middle class.
Keywords: D72; H26; 330; Tax evasion; redistribution; voting; Einkommensumverteilung; Einkommensteuerpolitik; Abstimmung; Steuervermeidung; Theorie